2018
DOI: 10.3390/brainsci8120223
|View full text |Cite
|
Sign up to set email alerts
|

Update on Insomnia after Mild Traumatic Brain Injury

Abstract: Sleep disturbance after traumatic brain injury (TBI) has received growing interest in recent years, garnering many publications. Insomnia is highly prevalent within the mild traumatic brain injury (mTBI) population and is a subtle, frequently persistent complaint that often goes undiagnosed. For individuals with mTBI, problems with sleep can compromise the recovery process and impede social reintegration. This article updates the evidence on etiology, epidemiology, prognosis, consequences, differential diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 84 publications
1
25
0
Order By: Relevance
“…27 Nonpharmacological interventions (eg, sleep hygiene recommendations such as a regular sleep schedule, keeping the bedroom dark, limiting noise) are often built into the care plan of the patient exhibiting postconcussive symptoms and have shown effectiveness in promoting optimal sleep behavior after concussion. 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Nonpharmacological interventions (eg, sleep hygiene recommendations such as a regular sleep schedule, keeping the bedroom dark, limiting noise) are often built into the care plan of the patient exhibiting postconcussive symptoms and have shown effectiveness in promoting optimal sleep behavior after concussion. 28…”
Section: Discussionmentioning
confidence: 99%
“…27 Nonpharmacological interventions (eg, sleep hygiene recommendations such as a regular sleep schedule, keeping the bedroom dark, limiting noise) are often built into the care plan of the patient exhibiting postconcussive symptoms and have shown effectiveness in promoting optimal sleep behavior after concussion. 28 Cognitive-behavioral therapy (CBT) has shown to be an effective treatment modality for improving school attendance and managing sleep symptoms after concussion. A study examining the effects of CBT on reduction of postconcussive symptoms in 31 patients aged 10 to 18 years revealed that 2 to 5 sessions of CBT improved persistent symptoms, including sleep symptoms, and thus school attendance in 97% of children following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ten participants were excluded from the analysis as they were over 30 years of age at the time of the attack. Two additional participants were excluded as they sustained mild traumatic brain injury (TBI) during the attack, which is associated with an increased risk of insomnia (Zhou & Greenwald, 2018 ). Thus, 336 participants were included in the analysis of present study.…”
Section: Methodsmentioning
confidence: 99%
“…VIP cells in the SCN receive light information from the retinohypothalamic tract and exert a powerful synchronizing effect on the rest of the SCN ( Hamnett et al, 2019 ). The coup-contrecoup injury associated with TBI may also affect the basal forebrain arousal area, damage the SCN, interrupt melatonin pathways, or disrupt thalamocortical connectivity, all of which have the potential to contribute to post-traumatic sleeping difficulties ( Zhou and Greenwald, 2018 ). Previous work has shown that the basal forebrain is involved in direct regulation of circadian rhythms in the SCN ( Yamakawa et al, 2016 ).…”
Section: Circadian Desynchrony and Tbi Symptomologymentioning
confidence: 99%